Analysis of the EFL Teaching process, recommended by the Ecuadorian Ministry of Education, applied for the development of speaking and listening skill in the language acquisition process of a student with mild mental retardation, at a local bilingual: School in the City of Guayaquil, School Year 2024 – 2025. - Salazar Palacio, Karen Nayely (2024)
This research study focuses on analyzing of the EFL teaching process, recommended by the Ecuadorian Ministry of Education, applied for the development of listening and speaking skill in the language acquisition process of a student with mild mental retardation at a local high school in Guayaquil. An observation of a class was carried out to know if the strategies suggested for curricular adaptation were taken into consideration. The researchers applied the methodology of qualitative research through a checklist, diagnostic test and an analysis of a lesson plan. The research findings showed that the teacher does not apply the strategies for curricular adaptation. It was also found that the high uses material resources that are not according to the level of English of the student with learning disability Mild Mental Retardation. Based on the findings, a proposal was created for providing strategies and activities that align with the curricular adaptation.